EVALUASI EFEK KONSUMSI MIE BIJI ALPUKAT GORENG DAN OSENG BUNCIS SERTA DAGING KAMBING TERHADAP KADAR GULA DARAH PENYANDANG NIDDM - Tejasari Tejasari (Faculty of Agricultural Technology, University of Jember, 2012)
Diabetes mellitus (DM) is a metabolic disease related to insulin deficient and or resistant that lead to hyperglycemic or blood glucose level higher than normal value (120 mg/100mL). Prolong hyperglikemc emerging the chronic effect such as retino, nefropati, and neuropati diabetic that decrease child growth and working performace. Balance diet with bioactive compound that stimulated pancreatic function or insulin secretion is one effort for stabilizing blood glucose level. This cross sectional research were aimed to evaluate the effect of functional diet of fried alvocado seed noodles,bean, and goat flash on blood glucose level of NIDDM subject. The functional diet consumed as breakfast for two weeks decreased blood glucose by 14.1 percent.Keywords : avocado noodle, functional diet, Diabetes mellitus(DM), blood glucose level